EMPOWERING YOUNG THINKERS: ENHANCING COMPUTATIONAL THINKING THROUGH PROBLEM POSING AND GEOGEBRA - Wardoyo, Gania Septiana; Hadi, Fida Rahmantika; Pradana, Lingga Nico (IAIN Ambon, 2025)
Despite the growing emphasis on computational thinking (CT) in mathematics education, few studies have explored how technology-assisted problem-posing approaches can effectively enhance CT skills among elementary students. This study aims to examine the effectiveness of the Problem Posing learning model assisted by GeoGebra in enhancing CT skills among fifth-grade elementary students. Utilizing a quantitative Interrupted Time Series design, the study involved 24 students. The intervention was implemented over ten weeks, with three mathematics sessions per week to facilitate interactive problem creation and exploration. Data were gathered using the Computational Thinking Test (CT-Test), administered before and after the intervention. The results showed an increase in the mean score from 69.38 (pre-test) to 83.54 (post-test), with statistically significant differences confirmed by a paired sample t-test (p < 0.001). Performance across CT indicators revealed the highest gains in abstraction and generalization, while debugging remained the lowest. Gender-based analysis indicated that female students slightly outperformed males in post-test scores, though both groups demonstrated significant improvement. These findings underscore the effectiveness of integrating problem posing and GeoGebra in fostering students’ CT skills, particularly in solving word problems in mathematics. This approach not only promotes conceptual understanding but also supports differentiated learning strategies.